MANAJEMEN PENDIDIKAN KARAKTER DISIPLIN TERHADAP PESERTA DIDIK DALAM PENINGKATAN MUTU PENDIDIKAN ISLAM - Afghor Fahruddin, Ahmad; Warti'ah, Warti'ah (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2023)
Character education is currently still not optimally applied in the world of education, especially since it has entered the era of the industrial revolution era 4.0 where conditions are open without knowing the limitations of distance and time and it is easier to access any information, this can cause students to experience character decline, and this will have a negative impact on the development of the nation. With conditions like now, the world of education is more effective in solving character problems in students, especially in disciplined character education. In the application of character education, good cooperation between schools and parents is needed, with good cooperation, it is hoped that character education, especially disciplinary characters, can be embedded in students. There are two factors that can influence and shape discipline in students, namely: first internal factors, second external factors, from these two factors in order to be formed in students there must be a bond of cooperation between the school, parents and the environment /community.